Extract of Scutellaria baicalensis inhibits dengue virus replication - Zandi, Keivan; Lim, Tong Hye; Rahim, Nor Aziyah; Shu, Meng Hooi; Teoh, Boon Teong; Sam, Sing Sin; Danlami, Mohammed Bashar; Tan, Kim Kee; AbuBakar, Sazaly (2015)
Scutellaria baicalensis (S. baicalensis) is one of the traditional Chinese medicinal herbs that have been shown to possess many health benefits. In the present study, we evaluated the in vitro antiviral activity of aqueous extract of the roots of S. baicalensis against all the four dengue virus (DENV) serotypes.Aqueous extract of S. baicalensis was prepared by microwave energy steam evaporation method (MEGHE™), and the anti-dengue virus replication activity was evaluated using the foci forming unit reduction assay (FFURA) in Vero cells. Quantitative real-time polymerase chain reaction (qRT-PCR) assay was used to determine the actual dengue virus RNA copy number. The presence of baicalein, a flavonoid known to inhibit dengue virus replication was determined by mass spectrometry.The IC50 values for the S. baicalensis extract on Vero cells following DENV adsorption ranged from 86.59 to 95.19 μg/mL for the different DENV serotypes. The IC50 values decreased to 56.02 to 77.41 μg/mL when cells were treated with the extract at the time of virus adsorption for the different DENV serotypes. The extract showed potent direct virucidal activity against extracellular infectious virus particles with IC50 that ranged from 74.33 to 95.83 μg/ mL for all DENV serotypes. Weak prophylactic effects with IC50 values that ranged from 269.9 to 369.8 μg/mL were noticed when the cells were pre-treated 2 hours prior to virus inoculation. The concentration of baicalein in the S. baicalensis extract was ~1% (1.03 μg/gm dried extract).Our study demonstrates the in vitro anti-dengue virus replication property of S. baicalensis against all the four DENV serotypes investigated. The extract reduced DENV infectivity and replication in Vero cells. The extract was rich in baicalein, and could be considered for potential development of anti-DENV therapeutics.